Power structures and patterns of interaction in the Malaysian Army - Khoo, Marcus Ghee Han; Bahiyah Abdul Hamid, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Study on power structures and their influences on the patterns of interaction used in the military is a rare phenomenon due to strong gatekeeping. Many past researchers have delved only into military culture and organisational communication. The aim of this paper is to present findings of this research gap i.e., on the patterns of interaction used by both commissioned officers and enlisted personnel in the Malaysian Army. It discusses how power structures influence the patterns of interaction used by them. The study investigates how rank structure and chain of command in the military (legitimised authority) influence both commissioned officers and enlisted personnel in deriving their patterns of interaction. It also investigates how the dominant ideology and organisational culture (hegemony) derive their patterns of interaction. This study analyses the transcripts of three audio recordings among commissioned officers and enlisted personnel which were audio recorded from a meet up, meeting and drill training session. The findings indicate that members of the Malaysian Army derive their patterns of interaction through different means. Those different means are not just through coercive means contrary to popular belief but also through regulatory and subtle means. Those different means are determined by the context and speakers. The findings reveal that command and control are essentially linked to many contributing factor and not just merely power per se.